The Framework in Risk Management Process: Lesson Learned from Hospital During Pandemic - Fery Agusman Motuho Mendrofa; sri Rusmini; Umi Hani; Sutrisno Sutrisno (GLOBAL HEALTH SCIENCE GROUP, 2022)
The pandemic situation poses great challenges for health care facilities such as rapidly changing hospitals in meeting the demands of infrastructure and operations. In addition to the need for adaptation related to the services provided, hospitals must be able to reduce the number of Covid-19 deaths as a top priority for health authorities. Uncertain conditions lead to the emergence of risks that cause losses so it is important to have risk management in hospitals This study was conducted to review risk management in hospitals in Semarang City that already have a framework for dealing with the COVID-19 pandemic and assess the impact of implementing the framework to the risk management process. This study is a cross-sectional study to see the relationship between the application of a risk management framework to the implementation of the Covid-19 risk management process in hospitals. The population in this study is all regulatory documents and reports on the implementation of the COVID-19 risk management process in hospitals in Semarang City in the period January 2020 to December 2021. Data is collected from documents and recording data in hospital related to regulations and risk management assessment instrument. Data were analyzed using Partial Least Square (PLS) software with SmartPLS 3.0 to test the hypothesis by looking at the probability value and its t-statistics. The study shows that the framework has a positive effect on the implementation of the risk management process in hospitals (T-Statistic > 1.96, p value < 0.05). The stronger the implementation of the COVID-19 risk management framework, the more positive the implementation of the COVID-19 risk management process will be.